Menstrual and fertility outcomes following the surgical management of postpartum haemorrhage: a systematic review. (9th December 2013) - Doumouchtsis, SK; Nikolopoulos, K; Talaulikar, VS; Krishna, A; Arulkumaran, S
<x xml:space="preserve">Abstract</x> Background Uterine‐sparing surgical interventions have long been practiced as an alternative to hysterectomy in the management of severe postpartum haemorrhage (PPH); however, the risks of impairment of subsequent fertility from such procedures are unclear. Objective To evaluate the menstrual and fertility outcomes following radiological or conservative surgical interventions for severe PPH. Search strategy A systematic review of English and non‐English articles using the Cochrane Library 2012, PubMed (1950–2012), Embase (1980–2012), and the National Research Register. The keywords used for our search included 'fertility', 'reproductive outcome', 'postpartum haemorrhage', 'embolisation', 'hypogastric artery ligation', 'B‐Lynch suture', 'stepwise uterine devascularisation', 'tamponade', and 'uterine compression sutures'. Selection criteria Studies including human female subjects with at least five cases. Data collection and analysis Independent extraction of articles by two authors using predefined data fields, including study quality indicators. Main results We identified 402 publications and after exclusions, 28 studies were included in the systematic review. Seventeen studies (675 women) reported on the fertility outcomes after uterine artery embolisation, five studies (195 women) reported on the fertility outcomes after uterine devascularisation, and six studies (125 women) reported on the fertility outcomes following uterine compression sutures. Overall, 553 out of 606 (91.25%) women resumed menstruation within 6 months of delivery. One hundred and eighty‐three out of 235 (77.87%) women who desired another pregnancy achieved conception. Author's conclusions Uterine‐sparing radiological and surgical techniques for the management of severe PPH do not appear to adversely affect the menstrual and fertility outcomes in most women; however, the number of studies and the quality of the available evidence is of concern.